2012
DOI: 10.1007/s10876-011-0437-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Stability, and Photoluminescence Properties of PdAu10(PPh3)8Cl2 Clusters

Abstract: We report on the synthesis, stability, and photoluminescence (PL) properties of triphenylphosphine (PPh 3 )-stabilized PdAu 10 (PPh 3 ) 8 Cl 2 cluster, which is a mono-Pd-doped cluster of the well-studied Au 11 (PPh 3 ) 8 Cl 2 cluster. The PdAu 10 (PPh 3 ) 8 Cl 2 cluster was synthesized by simultaneously reducing two different metal complexes; AuCl(PPh 3 ) and Pd(PPh 3 ) 4 . Experimental evaluation of the stability showed that PdAu 10 (PPh 3 ) 8 Cl 2 is more stable against degradation in solution than the mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…It is important to mention here that for this cluster the molecular peak with 4− charge has much lower intensity compared with the fragments seen in the lower mass range (m/z 100−1500). 32 Au 25 and Ag 44 are the most stable clusters reported so far, for the case of gold and silver, respectively. They have closed-shell electronic configuration consisting of 8 and 18 number of electrons.…”
Section: Section: Physical Processes In Nanomaterials and Nanostructuresmentioning
confidence: 89%
See 1 more Smart Citation
“…It is important to mention here that for this cluster the molecular peak with 4− charge has much lower intensity compared with the fragments seen in the lower mass range (m/z 100−1500). 32 Au 25 and Ag 44 are the most stable clusters reported so far, for the case of gold and silver, respectively. They have closed-shell electronic configuration consisting of 8 and 18 number of electrons.…”
Section: Section: Physical Processes In Nanomaterials and Nanostructuresmentioning
confidence: 89%
“…For example, the stable Au 25 (SR) 18 cluster shows a fragment in the mass spectrum due to the Au 4 (SR) 4 loss. 52 Even the stable Ag 44 (SR) 30 cluster, for which the crystal structure was determined recently, 35,36 shows several fragments due to Ag m (SR) n losses. It is important to mention here that for this cluster the molecular peak with 4− charge has much lower intensity compared with the fragments seen in the lower mass range (m/z 100−1500).…”
Section: Section: Physical Processes In Nanomaterials and Nanostructuresmentioning
confidence: 99%
“…However, since these metal clusters 30 are easily degraded in solution, their poor stability raises questions with regard to their viability as practical materials. 16 Thiolate-protected gold clusters (Au n (SR) m ), however, as reported in 1994 by Brust et al, 17 exhibit higher stability, due to the strong bonds formed between the metal and the thiolate 35 ligands. These clusters are stable even at high temperature in solution.…”
Section: Introductionmentioning
confidence: 93%
“…In addition to the thiolate‐protected Au‐Pd NCs in solution, naked Au‐Pd NCs in gas phase and phosphine‐protected Au‐Pd NCs in solution have also been studied extensively in the research community . Moreover, many studies have indicated the excellent catalytic activities of Au‐Pd and Au‐Pt NCs .…”
Section: Synthesis Of Monodisperse And/or Luminescent Bi‐mncsmentioning
confidence: 99%
“…The synthetic strategies for mono-MNCs have been well discussed in several review articles, [1][2][3][4][5][6]16,30,32,[50][51][52] and readers who are interested in that topic wileyonlinelibrary.com www.particle-journal.com www.MaterialsViews.com REVIEW in mono-MNCs, a number of monodisperse bi-MNCs have been successfully synthesized by using the Brust or Brust-like method. [34][35][36][37]47,52,[86][87][88][89][90][91][92][93][94][95][96][97][98] In general, two metal ions such as Au 3+ and Ag + , are simultaneously reduced by the addition of a certain amount of NaBH 4 , leading to the formation of bi-MNCs in the reaction solution. Similar to the mono-MNCs, where thiolated Au 25 , Au 38 , and Au 144 NCs are the most common and well-studied NC species because of their superior stability in solution, intriguing optical properties, well-defi ned and known cluster structures, and facile syntheses, bi-MNCs comprising of 25, 38, and 144 metal atoms are three most common species that have been synthesized by using the co-reduction method.…”
Section: Introductionmentioning
confidence: 99%